Bacteriological study of diabetic foot ulcer and it's relation to metabolic control in AL- Nassriah city /Iraq - A. Muter , Basim (University of Thi-Qar Journal of Science, 2012)
Background: Diabetes mellitus is a progressive disease; diabetic foot is the major complication of it, and eventually lead to development of gangrene and lower extremity amputation.Objective: To study the relative frequency of bacterial species cultured from diabetic foot infections and it's relation to the hypoglycemic treatment Patient and method: A case control study of 95 patients was included as two groups: Group 1: 45 hospitalized diabetic patients in AL-Hussein teaching hospital in AL-Nassriah city with diabetic foot lesions.Group 2 (control group): 50 diabetic patients but without diabetic foot lesions collected as outpatient from diabetic center in AL-Nassriah city. All the 95 patients were investigated with measurement of blood sugar (RBS) and HbA1C. Deep tissue biopsies were taken from the diabetic foot lesions of the 45 patients and were inoculated into freshly prepared thioglycollate broth medium. Bacterial species were identified by conventional bacteriological methods.Result: Clinical grading and bacteriological study of 45 patients with diabetic foot lesions revealed:Aerobic Gram-positive bacteria accounted for 71.2%. Staphylococcus aureus was the most frequent (37.8%) and Streptococci group A (20 %), and Staphylococcus epidermidis was regularly associated with the lesions (13.3 %). Gram-negative rods accounted for (24.4%). Pseudomonas aerogenosa was the most predominant gram negative bacilli (11.1 % ) , Escherichia coli (8.9 % ) and Enterobacter (4.5% ) , while undetected microorganism in diabetic foot ulcer was ( 4.4 % ) .